(untitled) (Research, Society and Development, 2022)
Animal origin flours is the non-edible by-product resulting from the processing of waste from the slaughter of animals, not intended for human consumption. In addition to taking advantage of waste, this process aims to reduce environmental damage. However, during some stage of the process of its elaboration may occur contamination by antimicrobials resistant microorganisms such as Salmonella spp. When serving as food for these animals, these products can spread pathogens on farms, causing flock infection. Food contaminated with Salmonella spp. antimicrobial resistant has a direct negative impact on poultry performance, as well as a risk to consumer health through carcass consumption. Thus, the aim of the present study was to investigate the antimicrobial resistance profile in Salmonella spp. isolated from non-edible animal from slaughterhouses located in Bahia and Pernambuco states, Brazil. From biochemical tests for isolation and identification of Salmonella spp., 81 isolates were randomly selected to be submitted to antimicrobial susceptibility testing using the plate diffusion method. Most of the isolates was sensitive to the antimicrobials tested. Nalidixic acid showed the highest percentage among those that were resistant, one of the antimicrobials used in the treatment of salmonellosis. This fact can be considered worrying, since the food production chain of animal origin can be an important carrier of resistant strains, especially since it is at the beginning of the production process.